ARTIFICIAL INTELLIGENCE IN POWER ELECTRONICS: TRENDS AND APPLICATIONS - K, Neelashetty; Dakulagi, Veerendra (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The integration of Artificial Intelligence (AI) in power electronics has revolutionized the design, control, and optimization of power conversion systems. AI-driven techniques, including machine learning, deep learning, and evolutionary algorithms, enhance efficiency, fault diagnosis, and predictive maintenance in modern power electronic systems. This paper presents a comprehensive review of emerging AI applications in power electronics, focusing on intelligent control strategies, real-time monitoring, and optimization techniques. Key trends, such as AI-enabled energy management in renewable power systems, adaptive control in electric drives, and predictive analytics for fault detection, are analyzed. Additionally, the paper highlights challenges, including computational complexity, data availability, and implementation constraints, while discussing future research directions for AI-driven advancements in power electronics.